IMPLEMENTASI METODE MURAJA’AH DAN TALAQQI DALAM PROGRAM TAHFIDZUL QURAN DI SMP MUHAMMADIYAH PK SURAKARTA - Ulfa Fauziah, Nurul; Ali Mustof, Triono a (Jurnal Bilqolam Pendidikan Islam, 2023)
This study aims to provide an overview of the implementation of the Qur'an tahfidz program at SMP Muhammadiyah PK Surakarta. This research uses qualitative phenomology method, the type of research uses field research. This research aims to provide an overview of the way the field of reality and can provide analysis, description and mapping of activities, processes and phenomena in accordance with the problems at the research location in detail, detail and depth. The subjects in this study involved the principal, Islamic Religious Education (PAI) teachers and students who participated in the program. Data collection techniques using observation, interview and documentation methods. Based on the results of the analysis, the implementation of the Muraja'ah and Talaqqi methods in the Tahfidzul Qur'an program at SMP Muhammadiyah PK Surakarta starts from the planning, implementation and assessment stages. The planning stage includes, the school establishes an Islamic school that includes the Tahfidzul Qur'an program as one of the superior programs, has a school vision and mission of the Tahfidzul Qur'an program that can improve the patience and quality of student memorization, and mentally prepares a teacher to be patient in teaching the Tahfidzul Qur'an program at school. The advantages of the methods implemented by teachers at SMP Muhammadiyah PK Surakarta, are able to increase student interest in participating in the Qur'an memorization program and are able to motivate students to remain istiqomah in memorizing the Qur'an. As for the shortcomings of using the method carried out, the emergence of insecure and embarrassed attitudes when answering the continued verses given by the teacher to students, as if students read the Qur'an even though they still have not memorized or are fluent in their reading. Overall, the results of this program evaluation can provide positive results and are of very good value